2016
DOI: 10.1002/pros.23269
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of LIM and SH3 Domain Protein 1 (LASP1) Negatively Regulated by Androgen Receptor Delays Castration Resistant Prostate Cancer Progression

Abstract: These results indicate that LASP1 is negatively regulated by AR at the transcriptional level and promotes tumor growth through induction of cell cycle, ultimately suggesting that LASP1 may be a potential target in prostate cancer treatment. Prostate 77:309-320, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The result revealed that cyclin D1 was also downregulated in these cells; however, phosphorylation of ERK was upregulated by drug treatment in BT-549 and UACC-812 cells (Figure 4c). Considering that the same phenomenon of increased ERK phosphorylation has been observed in a castration-sensitive prostate cancer cell line, LNCaP cells, in a previous study (Dejima et al, 2017), this might have been a result of negative feedback caused by growth inhibition induced by AR antagonists.…”
Section: Ar Antagonists Downregulated Cyclin D1 In Breast Cancer Cellssupporting
confidence: 75%
“…The result revealed that cyclin D1 was also downregulated in these cells; however, phosphorylation of ERK was upregulated by drug treatment in BT-549 and UACC-812 cells (Figure 4c). Considering that the same phenomenon of increased ERK phosphorylation has been observed in a castration-sensitive prostate cancer cell line, LNCaP cells, in a previous study (Dejima et al, 2017), this might have been a result of negative feedback caused by growth inhibition induced by AR antagonists.…”
Section: Ar Antagonists Downregulated Cyclin D1 In Breast Cancer Cellssupporting
confidence: 75%
“…In addition, our study showed that knockdown of LASP-1 expression induced G2 phase accumulation; besides, knockdown of LASP-1 leads to decreased expression of cyclin A and cyclin B, and increased phospho-cdc2 (Tyr15) expression (37). Our study demonstrated that silencing of LASP1 significantly inhibited prostate cancer cell growth by decreasing cyclin D1 and increasing p21 and p27 (38). Migration and invasion are key determinants of cancer cell progression and metastasis.…”
Section: Discussionmentioning
confidence: 59%
“…Further studies have reported that LASP1 is involved in cellular migration, invasion, proliferation and apoptosis through several mechanisms, such as participation in signaling pathways, m6A methylation modification or influencing the tumor microenvironment (30)(31)(32)(33)(34). In addition, progress has been made in terms of ongoing therapeutic research seeking to target LASP1 (35). Therefore, LASP1 is widely regarded as a prognostic marker for determining tumor prognosis (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%